Introduction - Editor-in-Chief (Thai Journal of Rheumatology, 2025)
The Thai Journal of Rheumatology proudly presents Volume 2, Issue 2, featuring a collection of diverse and valuable academic articles in the field of rheumatology. This issue aims to disseminate new knowledge and enhance understanding of important medical topics. The content includes an original article, "Cardiovascular Disease Prevalence and Risk in Rheumatoid Arthritis Patients: Insights from a Nationwide Thai Hospital Database," which provides insightful data on cardiovascular complications among rheumatoid arthritis patients in Thailand. Additionally, this issue features a comprehensive literature review titled "Geriatric Rheumatology," highlighting key aspects of rheumatologic care in the elderly population. Two noteworthy case reports, "Vasculitis Mimics Caused by Pythium Infection and Literature Review" and "A Case Report of Adult Type 2 Familial Hemophagocytic Lymphohistiocytosis," offer valuable clinical insights into rare and challenging conditions. To further engage readers, a quiz on the topic of "Crescent Sign" is also included, providing an opportunity for knowledge review and self-assessment. The editorial board sincerely hopes that this issue will be both academically enriching and practically beneficial for all readers. We also extend our heartfelt appreciation to all contributors for their ongoing support in maintaining the quality and relevance of the journal. Editor-in-Chief